Between a Rock and a Hard Place: Why Labor (Partially) Relinquished Its Institutional Resources in Belgium and the Netherlands - Oude Nijhuis, Dennie (Comparative studies in society and history, 2025)
Scholars have long recognized the importance of so-called “Ghent” systems of unemployment insurance for working-class strength and therefore national capitalist development. While only three European countries currently maintain “pure” Ghent systems, nearly a dozen did so during the first half of the last century. This article investigates the discontinuation of these systems in two paradigmatic cases, Belgium and the Netherlands. By focusing on the irreconcilable nature of trade union goals regarding the delivery, range, and funding of unemployment insurance, the analysis explains how the discontinuation of Ghent in these two countries could occur under distinctly union-friendly governments and with the explicit consent of their trade union movements. By showing that both the Belgian and Dutch trade union movements displayed great uncertainty regarding the organizational costs and benefits of assuming responsibility for benefit delivery, the article also explains why Belgium subsequently created a semi-Ghent system that continued to significantly boost union membership, while the Netherlands did not.